Digital workflow in full‐arch implant rehabilitation with segmented minimally veneered monolithic zirconia fixed dental prostheses: 2‐year clinical follow‐up. Issue 1 (9th August 2017) - Papaspyridakos, Panos; Kang, Kiho; DeFuria, Catherine; Amin, Sarah; Kudara, Yukio; Weber, Hans‐Peter
Abstract: Objective: To illustrate a digital workflow in full‐arch implant rehabilitation with minimally veneered monolithic zirconia and to report the outcomes including technical complications. Clinical Considerations: Three patients (5 edentulous arches) received full‐arch fixed implant rehabilitation with monolithic zirconia and mild facial porcelain veneering involving a digital workflow. The incisal edges and occluding surface areas were milled out of monolithic zirconia to reduce the possibility of chipping. Porcelain veneering was applied on the facial aspect to improve the esthetic result. Outcomes and technical complications are reported after 2 years of clinical and radiographic follow‐up. Conclusion: Implant and prosthesis survival rates were 100% after a short‐term follow‐up of 2 years. Technical complications were encountered in one patient. They did not adversely affect prosthesis survival or patient satisfaction and were easily addressed. A digital workflow for the design and fabrication of full‐arch monolithic zirconia implant fixed implant prostheses has benefits, but caution is necessary during CAD planning of the prosthesis to ensure a successful outcome. Long‐term clinical studies are needed to corroborate the findings discussed in this report. CLINICAL SIGNIFICANCE: This article presents an integrated digital workflow that was implemented for the implant‐prosthodontic rehabilitation of three edentulous patients with monolithic zirconia prostheses. Monolithic zirconia has been successfully incorporated in implant prosthodontics in an effort to reduce the technical complications associated with bilayered ceramics. This workflow simplifies design and fabrication of the zirconia prostheses. However, caution should be taken during CAD planning of the prosthesis to make sure the zirconia cylinder is sufficiently thick at the interface with the titanium insert. Additionally, when cutback is planned for facial porcelain veneering, the functional occluding cusps and incisal edges should be fabricated in monolithic zirconia to avoid chipping.